Factors predicting the 7-day period prevalence of low back pain among female undergraduate nursing students in an online learning environment: A multi-center cross-sectional study across Thailand - Summart, Ueamporn; Butsripoom, Benjamaporn; Polpanadham, Panicha; Palanupat, Thippawan; Piwpong, Ratchanee; Wittayapun, Yuwadee (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Most nursing students are female and represent a high-risk group for low back pain (LBP) before entering the workforce. However, the prevalence and specific predictors for LBP in this population remain poorly defined. Objective: This study investigated the prevalence and predictive factors of LBP among a nationally representative sample of Thai female nursing students. Methods: A cross-sectional online survey was conducted in 2022 among 3,490 female students from 18 nursing schools across Thailand. Data collected included demographics, online learning habits, psychological health, and LBP perceptions. Binary logistic regression was used to identify predictors of LBP. A p < 0.05 was deemed significant. Results: The seven-day period prevalence of LBP after six months of online learning was 39.5% (95% CI = 37.3-40.6). Factors significantly predicting LBP included anxiety [mild-to-moderate (AOR = 1.54, 95% CI = 1.31–1.82) and severe-to-extremely severe (AOR = 1.47, 95% CI = 1.13–1.91)], prolonged sitting (AOR = 1.52, 95% CI = 1.14–2.04), smartphone use for learning (AOR = 1.44, 95% CI = 1.23–1.68), bent posture (AOR = 1.33, 95% CI = 1.16–1.61), fatigue (per 10-point increase; AOR = 1.27, 95% CI = 1.11–1.46), and participation in online learning classes (AOR = 1.07, 95% CI = 1.02–1.12). Likewise, the final model demonstrated modest discriminatory power (AUC = 0.68, 95% CI = 0.63–0.74; p < 0.001). While the model significantly differentiates between students with and without LBP, its clinical utility is constrained by the condition’s multi-factorial nature. Conclusions: LBP is common among female nursing students and is driven by a combination of ergonomic and psychological factors. Nursing education programs should implement routine screening for both physical and mental well-being, alongside targeted preventive interventions to manage these modifiable risk factors before students enter professional practice.